S-C waveband heat-resistant wave-absorbing material and preparation method thereof

By preparing ZrTa/C composite materials by burning ZrTaMOF twice at 26-30V supply voltage, the problem of unsatisfactory wave absorption performance of S-C band is solved, and efficient wave absorption and high temperature stability is achieved. It is suitable for multi-band systems. .

CN119286471AActive Publication Date: 2025-01-10NAT UNIV OF DEFENSE TECH
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411209577.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-30
Publication Date
2025-01-10
Estimated Expiration
2044-08-30

AI Technical Summary

Technical Problem

The absorbing performance of existing absorbing materials in the S-C band is not ideal, especially the S-band cannot achieve the expected absorption effect, and environmental factors affect the performance stability, the preparation process is complex and costly, which limits its application.

Method used

Using ZrTaMOF as the precursor, nanoscale ZrTa/C composite absorbing materials are prepared by using two coking and heat-fired fires at a power supply voltage of 26-30V, including ZrO2, Ta2O5 and TaC nanocrystals, improving the absorption performance and thermal stability. .

Benefits of technology

It realizes efficient wave absorption capacity and excellent high temperature stability in the S-band, with reflection loss reaching -15.04dB and mass loss not exceeding 20%, which is suitable for multi-band systems.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119286471A_ABST
    Figure CN119286471A_ABST
Patent Text Reader

Abstract

The invention discloses an S-C wave band heat-resistant wave-absorbing material and a preparation method thereof, and relates to the technical field of S-C wave band wave-absorbing materials. The S-C wave band heat-resistant wave-absorbing material is prepared from ZrO2, Ta2O5 and a TaC nanocrystal, wherein the ZrO2 and the Ta2O5 are The preparation method comprises the following steps: S1, preparing ZrTa MOF powder by adopting a hydrothermal method; s2, the ZrTa MOF powder is subjected to two times of charring fast firing treatment, and the ZrTa / C composite material is obtained. According to the invention, ZrTa MOF is taken as a precursor, the ZrTa MOF is burnt twice under the power supply voltage of 26-30V, the nanoscale ZrTa / C composite wave-absorbing material is rapidly prepared, a novel wave-absorbing material which contains ZrO2, Ta2O5 and TaC nanocrystals and is resistant to high temperature and capable of effectively absorbing waves is obtained, and further, the electromagnetic parameters of the wave-absorbing material are improved by introducing Ta, so that S-waveband wave absorption is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of SC band wave absorbing materials, and in particular relates to an SC band heat-resistant wave absorbing material and a preparation method thereof. Background Art

[0002] In modern communications and radar systems, the S-band (2-4 GHz) and C-band (4-8 GHz) are two crucial frequency bands, widely used in satellite communications, weather monitoring, aviation navigation, and military reconnaissance. Consequently, there is a growing demand for absorbing materials that can effectively absorb electromagnetic waves in the SC band to counter reconnaissance.

[0003] While currently available absorbing materials on the market can, to a certain extent, meet the requirements of specific frequency bands (such as the X-band), significant challenges remain in their absorbing performance in the S-band and C-band, limiting their application in multi-band systems. Furthermore, the absorbing performance of many absorbing materials in the S-band and C-band is suboptimal, particularly in the S-band, where the expected absorption effect cannot be achieved, which directly impacts system performance. Environmental factors such as temperature and humidity significantly impact the performance of absorbing materials, causing performance fluctuations in actual use and making it difficult to maintain consistent absorbing effects. Furthermore, the preparation of high-performance absorbing materials often requires complex processes and expensive materials, which increases production costs and limits their widespread application.

[0004] Therefore, it is of great significance to develop a new type of absorbing material that has excellent absorbing performance in both S-band and C-band, good thermal stability, simple preparation process and controllable cost. Summary of the Invention

[0005] To address the above technical problems, the present invention proposes a heat-resistant SC-band absorbing material and preparation method. Using ZrTaMOF as a precursor, the nanoscale ZrTa / C composite absorbing material is rapidly prepared by rapidly pyrolyzing ZrTa MOF twice at a supply voltage of 26-30V. This yields a new high-temperature-resistant and effective absorbing absorbing material comprising ZrO2, Ta2O5, and TaC nanocrystals. Furthermore, the introduction of Ta in the present invention improves the electromagnetic parameters of the absorbing material, enabling S-band absorption.

[0006] The first aspect of the present invention discloses a method for preparing an SC band heat-resistant wave-absorbing material, wherein the SC band heat-resistant wave-absorbing material comprises ZrO2, Ta2O5 and TaC nanocrystals;

[0007] The preparation method comprises the following steps:

[0008] Step S1, preparing ZrTa MOF powder by a hydrothermal method;

[0009] Step S2, performing two pyrolysis treatments on the ZrTa MOF powder to obtain a ZrTa / C composite material;

[0010] The power supply voltage of the scorching fast burning is 26-30V, the time of each scorching fast burning is 1-2s, and the interval time between two scorching fast burnings is 11-12s.

[0011] According to the method for preparing the SC band heat-resistant wave absorbing material according to the first aspect of the present invention, step S1 includes the following sub-steps:

[0012] Step S11, weighing a certain amount of ZrCl4, TaCl4 and terephthalic acid and dissolving them in a certain volume of N,N-dimethylformamide to prepare a precursor solution, then transferring the precursor solution to a reactor, and then placing the reactor in an oven at 145-155°C to react for 8-10 hours. After the reaction is completed, the reactor is taken out and allowed to cool naturally at room temperature to obtain a solid product;

[0013] Step S12: centrifuging and washing the solid product, and finally drying the washed solid product to obtain ZrTa MOF powder.

[0014] According to the method for preparing the SC band heat-resistant absorbing material according to the first aspect of the present invention, in step S11, the mass concentration of the ZrCl4 is 20-27 mg / mL, and the mass ratio of the ZrCl4, TaCl4 and terephthalic acid is (3-4):(2-4):(4-6).

[0015] According to the method for preparing the SC band heat-resistant wave-absorbing material according to the first aspect of the present invention, in step S12, the solid product is first washed with N,N-dimethylformamide and then washed with ethanol.

[0016] According to the method for preparing the SC band heat-resistant wave absorbing material according to the first aspect of the present invention, in step S12, the cleaned solid product is dried in an oven at room temperature or at 60-80°C.

[0017] According to the method for preparing the SC band heat-resistant wave-absorbing material according to the first aspect of the present invention, in the step S2, the power supply voltage for the scorching heat is 27-29V.

[0018] According to the method for preparing the SC band heat-resistant wave absorbing material according to the first aspect of the present invention, in step S2, the scorching treatment process is specifically as follows:

[0019] A DC power supply is used as the energy supply. Two wires are led out from the positive and negative electrodes of the DC power supply and connected to two pieces of carbon cloth aligned vertically to form a loop. The ZrTa MOF powder is then placed between the two pieces of carbon cloth and subjected to a pyrolysis treatment in an inert gas atmosphere.

[0020] According to the method for preparing the SC band heat-resistant wave-absorbing material described in the first aspect of the present invention, the inert gas is argon or nitrogen.

[0021] The second aspect of the present invention discloses an SC band heat-resistant wave-absorbing material prepared by the aforementioned method for preparing the SC band heat-resistant wave-absorbing material, wherein the SC band heat-resistant wave-absorbing material comprises ZrO2, Ta2O5 and TaC nanocrystals.

[0022] According to the SC band heat-resistant wave-absorbing material described in the second aspect of the present invention, the sizes of the ZrO2, Ta2O5 and TaC nanocrystals are all 20-50nm.

[0023] According to the SC band heat-resistant absorbing material described in the second aspect of the present invention, the mass loss of the SC band heat-resistant absorbing material during the heating process from 200 to 1200° C. in an air atmosphere is no more than 20%.

[0024] The solution proposed by the present invention has the following technical effects:

[0025] The present invention uses ZrTa MOF as a precursor and rapidly prepares a nanoscale ZrTa / C composite absorbing material by twice pyrolyzing ZrTaMOF at a supply voltage of 26-30V. This yields a new high-temperature-resistant and effective absorbing absorbing material comprising ZrO2, Ta2O5, and TaC nanocrystals. The introduction of Ta can effectively regulate the electromagnetic parameters of the ZrTa / C composite material in the S band and improve the impedance matching capability of the composite material in the S band. Therefore, as much S-band electromagnetic wave incident on the material surface as possible enters the interior of the material without being reflected, thereby improving the material's absorbing capability in the S band.

[0026] In addition, the heat-resistant ZrTa / C composite absorbing material prepared by the present invention has a reflection loss of -15.04 dB at a frequency of 4 GHz in the S band.

[0027] In addition, the heat-resistant ZrTa / C composite absorbing material prepared by the present invention has a mass loss of no more than 20% during a temperature increase from 200°C to 1200°C in an air atmosphere, and has excellent high-temperature stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] In order to more clearly illustrate the specific embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the specific embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0029] Figure 1 This is a flow chart of a method for preparing an SC band heat-resistant absorbing material according to an embodiment of the present invention;

[0030] Figure 2 Scanning electron microscope images of ZrTa MOF at 10,000 times (a) and 30,000 times (b);

[0031] Figure 3 is the XRD pattern of ZrTa MOF;

[0032] Figure 4 Transmission electron microscopy images of the ZrTa / C composite material prepared in Example 1 of the present invention at scales of 200 nm (a), 100 nm (b), and 50 nm (c);

[0033] Figure 5 Transmission electron microscopy images of the ZrTa / C composite material prepared in Comparative Example 1 at scales of 200 nm (a), 100 nm (b), and 50 nm (c);

[0034] Figure 6 Transmission electron microscopy images of the ZrTa / C composite material prepared in Comparative Example 2 at scales of 200 nm (a), 100 nm (b), and 20 nm (c);

[0035] Figure 7 XRD patterns of the ZrTa / C composite materials prepared in Comparative Example 2(a), Comparative Example 1(b) and Example 1(c) of the present invention;

[0036] Figure 8 The Raman spectra of the ZrTa / C composite material prepared in Comparative Example 1(a) and Example 1(b) of the present invention are shown;

[0037] Figure 9 This is a thermogravimetric curve obtained by testing the ZrTa / C composite material prepared in Example 1 of the present invention in an air environment;

[0038] Figure 10 Graphs showing reflection loss of the ZrTa / C composite materials prepared in Example 1(a), Comparative Example 1(b) and Comparative Example 2(c) of the present invention. DETAILED DESCRIPTION

[0039] To make the objectives, technical solutions, and advantages of the embodiments of the present invention more clear, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the accompanying drawings of the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts shall fall within the scope of protection of the present invention.

[0040] A first aspect of this embodiment discloses a method for preparing an SC band heat-resistant wave-absorbing material, wherein the SC band heat-resistant wave-absorbing material includes ZrO 2 , Ta 2 O 5 and TaC nanocrystals.

[0041] like Figure 1 As shown, the preparation method comprises the following steps:

[0042] Step S1, preparing ZrTa MOF powder by a hydrothermal method.

[0043] Step S2: performing two pyrolysis treatments on the ZrTa MOF powder to obtain a ZrTa / C composite material.

[0044] Compared to the ZrO2 / C composite obtained by pyrolysis of a single-metal ZrMOF, the present invention introduces the Ta element to first obtain a bimetallic ZrTaMOF, which is then pyrolysis-treated to produce a ZrTa / C composite absorber containing three nanocrystals: ZrO2, Ta2O5, and TaC. The introduction of Ta effectively improves the electromagnetic parameters of the ZrTa / C composite in the S-band and enhances its impedance matching capability in the S-band. This allows for the maximum possible penetration of S-band electromagnetic waves incident on the material's surface into the material without being reflected, thereby enhancing the material's absorption capability in the S-band.

[0045] In step S1, ZrTa MOF powder is prepared by a hydrothermal method.

[0046] In some embodiments, step S1 includes the following sub-steps:

[0047] Step S11: weigh a certain amount of ZrCl4, TaCl4 and terephthalic acid and dissolve them in a certain volume of N,N-dimethylformamide to prepare a precursor solution. Then, the precursor solution is transferred to a reactor, and the reactor is placed in an oven at 145-155°C to react for 8-10 hours. After the reaction is completed, the reactor is taken out and allowed to cool naturally at room temperature to obtain a solid product.

[0048] Specifically, the reaction temperature of the reactor in the oven may be 145° C., 150° C., or 155° C. Preferably, the reaction temperature of the reactor in the oven is 150° C.

[0049] Specifically, the reaction time of the reactor in the oven can be 8 hours, 9 hours, or 10 hours. Preferably, the reaction time of the reactor in the oven is 9 hours.

[0050] Step S12: centrifuging and washing the solid product, and finally drying the washed solid product to obtain ZrTa MOF powder.

[0051] In some embodiments, in step S11, the mass concentration of ZrCl4 is 20-27 mg / mL, and the mass ratio of ZrCl4, TaCl4 and terephthalic acid is (3-4):(2-4):(4-6).

[0052] Specifically, the mass concentration of the ZrCl4 can be 20 mg / mL, 21 mg / mL, 22 mg / mL, 23 mg / mL, 24 mg / mL, 25 mg / mL, 26 mg / mL, or 27 mg / mL. Preferably, the mass concentration of the ZrCl4 is 23-25 ​​mg / mL.

[0053] In some embodiments, in step S12, the solid product is first washed with N,N-dimethylformamide and then washed with ethanol to remove residual organic matter.

[0054] In some embodiments, in step S12, the washed solid product is dried at room temperature or in an oven at 60-80°C.

[0055] In step S2, the ZrTa MOF powder is subjected to two pyrolysis treatments to obtain a ZrTa / C composite material.

[0056] In some embodiments, in step S2, the scorching and rapid burning treatment process is specifically as follows:

[0057] A DC power supply is used as the energy supply. Two wires are led out from the positive and negative electrodes of the DC power supply and connected to two pieces of carbon cloth aligned vertically to form a loop. The ZrTa MOF powder is then placed between the two pieces of carbon cloth and subjected to a pyrolysis treatment in an inert gas atmosphere.

[0058] In some embodiments, the inert gas is argon or nitrogen.

[0059] Preferably, the carbon is placed in a glass container, and Ar is introduced into the glass container to exclude air, thereby providing an Ar atmosphere.

[0060] In some embodiments, the power supply voltage of the scorch burn is 26-30V, the duration of each scorch burn is 1-2 seconds, and the interval between two scorch burns is 11-12 seconds.

[0061] When the pyrolysis voltage is less than 26V, the ZrTa MOF framework does not completely collapse, and some Zr and Ta act as catalysts, catalyzing the decomposition of terephthalic acid and producing carbon nanotubes. Furthermore, when the voltage is too low, the ZrTa MOF framework cannot completely decompose into carbon, resulting in a weak conductive loss. When the pyrolysis voltage is greater than 30V, the organic matter in the ZrTa MOF framework vaporizes and volatilizes at high temperatures, preventing the desired ZrTa / C composite material from being obtained.

[0062] At the same time, the present invention performs two pyrolysis fast firings on the ZrTa MOF framework so that the MOF framework can completely collapse to produce ZrO2, Ta2O5 and TaC nanocrystals. However, in order to prevent the ZrO2, Ta2O5 and TaC nanocrystals from agglomerating under continuous high temperature, the interval time between the two pyrolysis fast firings is 11-12 seconds, so that the ZrO2, Ta2O5 and TaC nanocrystals formed at high temperature have no time to continue to agglomerate before the reaction process is cooled, thereby achieving uniform loading of ZrO2, Ta2O5 and TaC nanocrystals with a size of 20-50 nm on the thin layer of carbon.

[0063] Specifically, the power supply voltage of the scorch burner can be 26 V, 27 V, 28 V, 29 V and 30 V. Preferably, the power supply voltage of the scorch burner is 27-29 V. Further preferably, the power supply voltage of the scorch burner is 28 V.

[0064] Specifically, the time for each scorching fast burning can be 1 second, 1.5 seconds, or 2 seconds. Preferably, the time for each scorching fast burning is 2 seconds.

[0065] Specifically, the interval time between two scorching fast burnings can be 11s, 11.5s, or 12s.

[0066] The second aspect of this embodiment discloses an SC-band heat-resistant wave-absorbing material prepared by the aforementioned method for preparing the SC-band heat-resistant wave-absorbing material. The SC-band heat-resistant wave-absorbing material includes ZrO2, Ta2O5, and TaC nanocrystals.

[0067] In some embodiments, the sizes of the ZrO2, Ta2O5 and TaC nanocrystals are all 20-50 nm.

[0068] In some embodiments, the mass loss of the SC band heat-resistant absorbing material during a temperature increase from 200° C. to 1200° C. in an air atmosphere is no greater than 20%.

[0069] Example 1

[0070] (1) 0.3-0.4 g ZrCl4, 0.2-0.4 g TaCl4 and 0.4-0.6 g terephthalic acid were added to 15 ml N, N-dimethylformamide in sequence and stirred thoroughly by ultrasonication to obtain a precursor solution. The precursor solution was then transferred to a reactor, and the reactor was placed in an oven at 145-155 ° C. to react for 8-10 hours. After the reaction was completed, the reactor was taken out and allowed to cool naturally at room temperature to obtain a solid product;

[0071] (2) The solid product is centrifuged and washed multiple times using a centrifuge and N,N-dimethylformamide and / or ethanol, and finally the washed solid product is dried at room temperature or in an oven at 60-80° C. to obtain ZrTa MOF powder.

[0072] (3) A DC power supply is used as the power supply, two wires are drawn out from the positive and negative electrodes of the DC power supply, and are respectively connected to two pieces of carbon cloth aligned up and down to form a loop. Then, the ZrTa MOF powder is placed between the two pieces of carbon cloth, and the ZrTa MOF powder is subjected to two pyrolysis fast calcination treatments in an argon atmosphere to obtain a ZrTa / C composite material as an SC band heat-resistant wave absorbing material.

[0073] The power supply voltage of the scorching heat fast burning is 28V, the time of each scorching heat fast burning is 2s, and the interval time between two scorching heat fast burning is 11s.

[0074] Comparative Example 1

[0075] The difference from Example 1 is that the power supply voltage of the scorching fast burning is 22V.

[0076] Comparative Example 2

[0077] The difference from Example 1 is that the power supply voltage of the scorch fast burning is 16V.

[0078] Figure 2 The scanning electron microscope photos of ZrTa MOF magnified 10,000 times (a) and 30,000 times (b). Figure 2 It can be seen that ZrTaMOF has a regular polyhedral shape and a particle size of approximately 200-500nm.

[0079] Figure 3Figure 2 is the XRD pattern of ZrTa MOF. The peaks at 22.31°, 25.78°, and 30.77° in the spectrum are attributed to the (115), (224), and (046) crystal planes, corresponding to the typical characteristic peaks of Zr-based MOF materials, confirming the successful preparation of ZrTa MOF.

[0080] Figure 4 The transmission electron microscope images of the ZrTa / C composite material prepared in Example 1 of the present invention are taken at 200nm (a), 100nm (b), and 50nm (c) scales. Figure 4 It can be seen that the particle size of the nanocrystals in the ZrTa / C composite material obtained in Example 1 is 20-50 nm, and is uniformly supported on the carbon substrate.

[0081] Figure 5 The transmission electron microscope images of the ZrTa / C composite material prepared in Comparative Example 1 are at 200nm (a), 100nm (b), and 50nm (c) scales. Figure 5 It can be seen that the particle size of the nanocrystals in the ZrTa / C composite material obtained in Comparative Example 1 is 10-20 nm, which is smaller than that in Example 1. This is because the supply voltage in Comparative Example 1 is 22 V, compared to 28 V in Example 1. The upper temperature limit is lower than that in Example 1, and therefore the degree of supercooling is also lower. This results in a low nucleation rate of Zr and Ta in the material, and Zr and Ta are not easily coarsened and grown. Therefore, the particle size of the nanocrystals in the composite material is smaller than that in Example 1.

[0082] Figure 6 The transmission electron microscope images of the ZrTa / C composite material prepared in Comparative Example 2 are at 200nm (a), 100nm (b), and 20nm (c) scales. Figure 6 It can be seen that the microstructure of the ZrTa / C sample prepared in Comparative Example 2 still retains some of the ZrTa MOF microstructure, indicating that it has not completely decomposed. Furthermore, the microstructure of the ZrTa / C composite material prepared in Comparative Example 2 produces elongated carbon nanotubes, indicating that during the 16V pyrolysis process, Zr and Ta acted as catalysts, catalyzing the decomposition of terephthalic acid and producing a large number of carbon nanotubes. Furthermore, the ZrTa nanocrystals in the ZrTa / C prepared by 16V pyrolysis are smaller, at 2-5nm.

[0083] Figure 7 The XRD patterns of the ZrTa / C composite materials prepared in Comparative Example 2(a), Comparative Example 1(b) and Example 1(c) of the present invention are shown in FIG. Figure 7It can be seen that when the ZrTa MOF sample was pyrolyzed at 16V, it did not completely decompose at low temperatures and still maintained characteristic diffraction peaks similar to those of ZrTa MOF, indicating that ZrTa MOF has good thermal stability. However, when the ZrTa MOF was pyrolyzed at 22V and 28V, the XRD pattern of the final product showed significant changes. The XRD pattern of the sample heated at 22 V shows peaks at 22.962°, 28.493°, 36.867°, and 50.403°, corresponding to Ta2O5 (PDF 18-1304). The peaks at 29.721° and 56.662° also correspond to Ta2O5 (PDF 54-0514). This indicates that Ta in the ZrTa / C composite obtained at 22 V exists in the form of Ta2O5 and Zr in the form of ions. This is because the oxidation of Zr to ZrO2 requires a higher temperature, which also reflects the high-temperature stability of Zr. Under low voltage conditions, the upper temperature limit is insufficient, so Zr cannot react to ZrO2. The XRD pattern of the sample heated at 28 V shows peaks at 30.119°, 50.219°, and 62.678°, corresponding to ZrO2 (PDF The peaks at 22.692°, 28.493°, and 36.867° correspond to Ta2O5 (PDF18-1304); and the peaks at 34.85°, 40.46°, 58.55°, and 70.0° correspond to TaC (PDF 35-0801). This demonstrates that the ZrTa / C composite material obtained at 28 V contains ZrO2, Ta2O5, and TaC nanocrystals.

[0084] Figure 8 The Raman spectra of the ZrTa / C composite material prepared in Comparative Example 1(a) and Example 1(b) of the present invention are shown in FIG. -1 and 1590cm -1 The peaks of the spectrum correspond to the D peak and G peak of carbon, and their intensity is expressed as I D and I G Indicates. 1350cm -1 The peak is attributed to disordered carbon, which is related to the disordered sp 3 Hybrid carbon related; 1590 cm -1 Peak and ordered sp 2 Hybrid graphitic carbon related. D and I G The ratio is used to characterize the structural defects and disorder degree of the material. Figure 8It can be seen that the peak ratio of the ZrTa / C sample obtained by pyrolysis of the ZrTa MOF at a voltage of 22 V is 0.911, and the peak ratio of the ZrTa / C sample obtained by pyrolysis of the ZrTa MOF at a voltage of 28 V is 0.929. In other words, as the pyrolysis voltage increases, the peak ratio increases, indicating that compared with comparative example 1, the ZrTa / C composite material obtained in Example 1 of the present invention has an improved defect structure and enhanced polarization loss capacity.

[0085] Figure 9 Thermogravimetric curve of the ZrTa / C composite material prepared in Example 1 of the present invention obtained by testing in an air environment. Figure 9 It can be seen that before 400°C, the ZrTa / C composite material loses weight slightly, which is caused by the evaporation of water molecules adsorbed in the ZrTa / C composite material; between 400-700°C, the ZrTa / C composite material loses no more than 20% of its mass, which is caused by further reaction of carbon at high temperature; after 700°C, the ZrTa / C composite material no longer loses mass. However, compared with current research, the ZrTa / C obtained by 28V heat treatment still shows excellent thermal stability, because most of the thermal stability experiments of MOFs diffraction absorbing materials are currently carried out in an inert gas atmosphere, and the mass loss is as high as 40%; while the thermal stability of the ZrTa / C composite material of the present invention is carried out in an air atmosphere, and its loss is still no more than 20% when the temperature is raised to 1200°C, which proves the excellent high-temperature stability of the ZrTa / C sample.

[0086] Figure 10 The reflection loss diagram of the ZrTa / C composite material prepared in Example 1(a), Comparative Example 1(b) and Comparative Example 2(c) of the present invention is shown. A reflection loss lower than -10dB indicates that the sample can achieve 90% absorption of electromagnetic waves in this frequency band. Figure 10It can be seen that the ZrTa / C composite material of Example 1 of the present invention has a maximum reflection loss of -15.04dB at a frequency of 4GHz at a thickness of 3.6mm. At a thickness of 3.4mm, the frequency band in which the reflection loss reaches -10dB is 3.84-5.08GHz, and the effective bandwidth reaches 1.2GHz. Overall, the operating bands of the ZrTa / C composite material of Example 1 of the present invention are 3.53GHz-5.4GHz and 15.7-17GHz, which are the SC band and Ku band. The maximum reflection loss value in the S band reaches -15dB, which has application prospects. The sample of Comparative Example 1 has a maximum reflection loss of -27.7dB at a frequency of 5.73GHz at a thickness of 3.4mm. At a thickness of 2.8mm, the frequency band in which the reflection loss reaches -10dB is 5.65-7.7GHz, and the effective bandwidth reaches 2GHz. Overall, the operating band of the sample of Comparative Example 1 is 4.4GHz-8.2GHz, which is the C band. The sample in Comparative Example 2 has a maximum reflection loss of -24.2dB at a frequency of 16.64GHz at a thickness of 2.2mm. At a thickness of 2.2mm, the frequency range in which the reflection loss reaches -10dB is 15.-18GHz, and the effective bandwidth reaches 3GHz. Overall, the sample in Comparative Example 2 operates in the Ku band of 13GHz-18GHz.

[0087] Example 2

[0088] The difference from Example 1 is that the power supply voltage of the scorching fast burning is 26V.

[0089] Example 3

[0090] The difference from Example 1 is that the power supply voltage of the scorching fast burning is 27V.

[0091] Example 4

[0092] The difference from Example 1 is that the power supply voltage of the scorching fast burning is 29V.

[0093] Example 5

[0094] The difference from Example 1 is that the power supply voltage of the scorching fast burning is 30V.

[0095] Example 6

[0096] The difference from Example 1 is that the time for each scorching fast burning is 1 second, and the interval between two scorching fast burnings is 12 seconds.

[0097] Example 7

[0098] The difference from Example 1 is that the time for each rapid burning is 1.5 seconds, and the interval between two rapid burnings is 11.5 seconds.

[0099] In summary, the solution proposed in the present invention has the following technical effects:

[0100] The present invention uses ZrTa MOF as a precursor and rapidly prepares a nanoscale ZrTa / C composite absorbing material by twice pyrolyzing ZrTaMOF at a supply voltage of 26-30V. This yields a new high-temperature-resistant and effective absorbing absorbing material comprising ZrO2, Ta2O5, and TaC nanocrystals. The introduction of Ta can effectively regulate the electromagnetic parameters of the ZrTa / C composite material in the S band and improve the impedance matching capability of the composite material in the S band. Therefore, as much S-band electromagnetic wave incident on the material surface as possible enters the interior of the material without being reflected, thereby improving the material's absorbing capability in the S band.

[0101] In addition, the heat-resistant ZrTa / C composite absorbing material prepared by the present invention has a reflection loss of -15.04 dB at a frequency of 4 GHz in the S band.

[0102] In addition, the heat-resistant ZrTa / C composite absorbing material prepared by the present invention has a mass loss of no more than 20% during a temperature increase from 200°C to 1200°C in an air atmosphere, and has excellent high-temperature stability.

[0103] Please note that the technical features of the above embodiments can be combined arbitrarily. In order to make the description concise, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification. The above embodiments only express several implementation methods of the present application. The description is relatively specific and detailed, but it cannot be understood as a limitation on the scope of the invention patent. It should be pointed out that for ordinary technicians in this field, without departing from the concept of this application, several variations and improvements can be made, which all fall within the scope of protection of this application. Therefore, the scope of protection of the patent in this application shall be based on the attached claims.

Claims

1. A method for preparing a SC band heat-resistant wave absorbing material, characterized in that: The SC band heat-resistant wave absorbing material includes ZrO2, Ta2O5 and TaC nanocrystals; The preparation method comprises the following steps: Step S1, preparing ZrTa MOF powder by hydrothermal method; Step S2, performing two pyrolysis treatments on the ZrTa MOF powder to obtain a ZrTa / C composite material; The power supply voltage of the scorching heat fast burning is 26-30V, the time of each scorching heat fast burning is 1-2s, and the interval time between two scorching heat fast burning is 11-12s.

2. The method for preparing the SC band heat-resistant wave absorbing material according to claim 1, characterized in that: The step S1 comprises the following sub-steps: Step S11, weigh a certain amount of ZrCl4, TaCl4 and terephthalic acid and dissolve them in a certain volume of N,N-dimethylformamide to prepare a precursor solution, then transfer the precursor solution to a reactor, and then put the reactor into an oven at 145-155° C. to react for 8-10 hours. After the reaction is completed, take out the reactor and let it cool naturally at room temperature to obtain a solid product; Step S12, centrifuging and washing the solid product, and finally drying the washed solid product to obtain ZrTa MOF powder.

3. The method for preparing the SC band heat-resistant wave absorbing material according to claim 2, characterized in that: In the step S11, the mass concentration of ZrCl4 is 20-27 mg / mL, and the mass ratio of ZrCl4, TaCl4 and terephthalic acid is (3-4):(2-4):(4-6).

4. The method for preparing the SC band heat-resistant wave absorbing material according to claim 2, characterized in that: In the step S12, the solid product is firstly washed with N,N-dimethylformamide, and then washed with ethanol.

5. The method for preparing the SC band heat-resistant wave absorbing material according to claim 2, characterized in that: In the step S12, the washed solid product is dried at room temperature or in an oven at 60-80°C.

6. The method for preparing the SC band heat-resistant wave absorbing material according to claim 1, characterized in that: In the step S2, the power supply voltage of the scorching heat fast burning is 27-29V.

7. The method for preparing the SC band heat-resistant wave absorbing material according to claim 1, characterized in that: In step S2, the scorching and rapid burning treatment process is specifically as follows: A DC power supply is used as an energy supply, two wires are led out from the positive and negative electrodes of the DC power supply, and are respectively connected to two pieces of carbon cloth aligned up and down to form a loop, and then the ZrTa MOF powder is placed between the two pieces of carbon cloth, and the ZrTa MOF powder is subjected to a pyrolysis treatment in an inert gas atmosphere.

8. The method for preparing the SC band heat-resistant wave absorbing material according to claim 7, characterized in that: The inert gas is argon or nitrogen.

9. An SC band heat-resistant wave-absorbing material prepared by the method for preparing an SC band heat-resistant wave-absorbing material according to any one of claims 1 to 8, characterized in that: The sizes of the ZrO2, Ta2O5 and TaC nanocrystals are all 20-50nm.

10. The SC band heat-resistant wave absorbing material according to claim 9, characterized in that: The mass loss of the SC band heat-resistant wave-absorbing material during the temperature rise process from 200 to 1200° C. in an air atmosphere is no more than 20%.

Citation Information

Patent Citations

  • Low thermal conductivity ceramic Mg6ZrTa4O18 and preparation method thereof

    CN106083041A

  • Ultrahigh-temperature wave-absorbing composite material as well as preparation method and application thereof

    CN112521911A

  • Nanometer ZrO2 / C heat-resistant wave-absorbing material and preparation method thereof

    CN116081686A

  • Radiowave absorber

    EP2645481A1

  • Microwave exothermic body and its manufacturing method

    JP2006024502A